Pengaruh Latihan Koordinasi dan Reaksi terhadap Akurasi dan Kecepatan Servis Spin pada Atlet Tenis Junior - Ians Aprilo; Poppy Elisano Arfanda (Pusat Pengembangan Olahraga Universitas Pahlawan, 2026)
Purpose of the study: This study aims to analyze the effect of coordination training and visual reaction training on improving the accuracy and speed of spin serves in junior tennis athletes in Makassar. Materials and methods: The research design used a quasi-experimental approach with a pretest–posttest control group model involving 20 athletes, divided into two groups: coordination training and visual reaction training. The training program was conducted over six weeks with a frequency of three times per week. Results: he t-test results showed a significant improvement in all variables (p < 0.05). Coordination training increased accuracy by 13.4%, while visual reaction training increased serve speed by 10.8%. ANOVA tests showed significant differences between groups on both variables. Conclusions: It can be concluded that both types of training are effective in improving spin serve performance, with coordination training having a greater effect on accuracy, while visual reaction training is more dominant in serve speed.